DESIGN OF EDUCATIONAL RECYCLING WASTE MANAGEMENT VIDEO GAME FOR CHILDREN - Setyawati, Endang; Paath, David Kristian; Komala, Evelyne Kristiani (International Journal of Business and Information Technology, 2020)
As time goes by, the earth has undergone many changes, many of which have happened, from natural changes to human lifestyle. Many natural disasters occur as a result of the development of human lifestyles, such as floods caused by littering and piling up. Littering is one of the causes of flooding, therefore it is necessary to build awareness of society, especially children as the next generation. The purpose of " Design of Educational Recycling Waste Management Video Games For Children " is to provide an understanding of waste and be able to find out the products of reusing inorganic and organic waste to children. The benefits of designing interesting video games can stimulate children's psychology in understanding the cleanliness of the environment and provide education that waste can be used. The research method in this design uses the Research and Development method which is used to produce a product and test the effectiveness of the product. The results obtained are that there is a significant difference in children's understanding of waste when playing video games and before playing so that the use of games as educational media can be said to be effective.